New Insights on Slavic God Volosъ / Velesъ from a Vedic PerspectiveNovi uvidi o staroslovenskom bogu Volosu / Velesu iz vedske perspektive - Ivanković, Milorad (Studia mythologica Slavica, 2019)
<span style="line-height: 115%; font-family: 'Helvetica','sans-serif'; font-size: 11pt; mso-fareast-font-family: Calibri; mso-fareast-theme-font: minor-latin; mso-bidi-font-family: AGaramondPro-Italic; mso-ansi-language: SL; mso-fareast-language: EN-US; mso-bidi-language: AR-SA; mso-bidi-font-style: italic;">In 1973, Ivanov and Toporov developed an attempted reconstruction of the presumably central theme of ancient Slavic mythology, viz. the cosmic battle between the thunder-god Perunъ and his adversary Volosъ the cattle god, modelled after the analogous examples taken from Baltic folklore and Vedic mythology, whereby the Slavic god Volosъ was identified with the Vedic demon, Vala. On the same footing, in 2008, came Katičić with similar results, but he identified the Slavic god Volosъ with the Vedic demon Vr̥tra. However, the evidence from the primary Vedic and Sanskrit sources presented in this treatise soundly disproves the above interpretations and identifications and reveals quite a different image of the Slavic god.